A comparison of the trauma and autobiographical narratives of female rape and non-sexual assualt survivors - Edross, Sadia (Department of Psychology, 2014)
Research on the trauma and autobiographical narratives of survivors are two burgeoning areas in the international literature. The focus is primarily on the correlation between particular linguistic features in these narratives and PTSD and depression. Whilst these findings have important clinical implications, feminists and critical psychologists argue that an emphasis on a medical trauma response model for understanding narratives attenuates the influence of socio-cultural context and subjective differences. The primary aim of the current study was to explore whether there were commonalities and differences in the trauma and autobiographical narratives in a sample of South African adult female survivors of sexual and non-sexual assault. A broader aim of the study was to be attentive to the interconnection and influence of multiple factors on the narratives of the participants.